2016
DOI: 10.1155/2016/8901518
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Helminth Parasites in Intestines and Their Seasonal Rate of Infestation in Three Freshwater Fishes of Kashmir

Abstract: The present study was undertaken to determine the incidence of helminth parasites in fishes with special reference to water quality parameters in Dal Lake and River Jhelum and correlate the observations. Water, fish, and parasite samples were collected during different seasons from various sites and processed. Three fish species, namely, Schizothorax niger Heckel 1838, Schizothorax esocinus Heckel 1838, and Schizothorax curvifrons Heckel 1838, were recovered from these water bodies. The physicochemical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Conventional fishing methods with the ability to destroy the plankton community in the lagoon, thereby enhancing food competition and other environmental stressors arising from anthropogenic activities along the shores, are other reasons that may be ascribed to the prevalence of parasitic infection in this study [ 48 ]. Furthermore, significantly higher intensity of infection by acanthocephalans in male fish than in female fish have been previously reported [ 49 , 50 ]. The influence of sex on the susceptibility of animals to infections may be due to genetic predisposition and differential susceptibility owing to hormonal control, sampling season and geographical differences [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Conventional fishing methods with the ability to destroy the plankton community in the lagoon, thereby enhancing food competition and other environmental stressors arising from anthropogenic activities along the shores, are other reasons that may be ascribed to the prevalence of parasitic infection in this study [ 48 ]. Furthermore, significantly higher intensity of infection by acanthocephalans in male fish than in female fish have been previously reported [ 49 , 50 ]. The influence of sex on the susceptibility of animals to infections may be due to genetic predisposition and differential susceptibility owing to hormonal control, sampling season and geographical differences [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, significantly higher intensity of infection by acanthocephalans in male fish than in female fish have been previously reported [ 49 , 50 ]. The influence of sex on the susceptibility of animals to infections may be due to genetic predisposition and differential susceptibility owing to hormonal control, sampling season and geographical differences [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 95%
“…For instance, temperature affects both the development time of acanthocephalan parasites in their intermediate hosts 58 , 59 and their prevalence and abundance in their definitive fish hosts 60 . This is reflected in field studies having reported seasonal effects in the prevalence and intensity of infection with acanthocephalans in both intermediate and definitive hosts 61 65 . So far, however, only a limited number of studies have provided evidence for a joint effect of temperature and infection with acanthocephalan parasites on the ecological role of their intermediate host species.…”
Section: Introductionmentioning
confidence: 99%
“…Helminths are one of the major parasite groups infecting fish and are a major cause of losses in fish farming (Wali et al, 2016). Cestodes and acanthocephalans are particularly well known for inflicting severe damage due to their deep penetration into the gut tissue of their hosts (Dezfuli, Bosi, DePasquale, Manera, & Giari, 2016).…”
Section: Introductionmentioning
confidence: 99%